Modelling and Optimization Containers Dwell-Time in Tanjung Priok Port Indonesia - Aryo De Wibowo; Efendi Efendi (Institut Manajemen Wiyata Indonesia, 2019)
Import containers stay too long, around 6.2 days at container terminals in Indonesia, which is negatively affecting logistics cost and is causing a serious adverse effect in terms of logistic costs for domestic businesses and prices paid by consumers. In this paper, we propose a method which controls and reduces dwell-time of import containers in The Port of Tanjung Priok. The controlled object is modeled as a reengineering business proses of import containers which controls time duration, processes and weights. Experimental results demonstrate the optimization of the proposed method and reduce the dwell-time.